Inflammatory potential of the diet and risk of colorectal cancer in the European Prospective Investigation into Cancer and Nutrition study. Issue 4 (31st January 2020) - Jakszyn, Paula; Cayssials, Valerie; Buckland, Genevieve; Perez‐Cornago, Aurora; Weiderpass, Elisabete; Boeing, Heiner; Bergmann, Manuela M.; Vulcan, Alexandra; Ohlsson, Bodil; Masala, Giovanna; Cross, Amanda J.; Riboli, Elio; et al.
Abstract : Proinflammatory diets are associated with risk of developing colorectal cancer (CRC), however, inconsistencies exist in subsite‐ and sex‐specific associations. The relationship between CRC and combined lifestyle‐related factors that contribute toward a low‐grade inflammatory profile has not yet been explored. We examined the association between the dietary inflammatory potential and an inflammatory profile and CRC risk in the European Prospective Investigation into Cancer and Nutrition (EPIC) study. This cohort included 476, 160 participants followed‐up of 14 years and 5, 991 incident CRC cases (3, 897 colon and 2, 094 rectal tumors). Dietary inflammatory potential was estimated using an Inflammatory Score of the Diet (ISD). An Inflammatory Profile Score (IPS) was constructed, incorporating the ISD, physical activity level and abdominal obesity. The associations between the ISD and CRC and IPS and CRC were assessed using multivariable regression models. More proinflammatory diets were related to a higher CRC risk, particularly for colon cancer; hazard ratio (HR) for highest versus lowest ISD quartile was 1.15 (95% confidence interval [CI] 1.04–1.27) for CRC, 1.24 (95% CI 1.09–1.41) for colon cancer and 0.99 (95% CI 0.83–1.17) for rectal cancer. Associations were more pronounced in men and not significant in women. The IPS was associated with CRC risk, particularly colon cancer among men; HRs for the highest versus lowest IPS was 1.62 (95% CI 1.31–2.01) for colon cancer overall and 2.11 (95% CI 1.50–2.97) for colon cancer in men. Our study shows that more proinflammatory diets and a more inflammatory profile are associated with higher risk of CRC, principally colon cancer and in men. Abstract : What's new? Chronic inflammation has been implicated in colorectal cancer (CRC), and diet plays an important role in modulating systemic inflammation. Two additional factors that contribute to chronic inflammation and also increase CRC risk are adiposity and lack of physical activity. In this large prospective study, the authors gained further insight into these relationships. They found that pro‐inflammatory diets and a higher Inflammatory Profile Score (IPS, based on diet, physical activity, and abdominal obesity) are strong predictors of CRC, but principally of colon cancer and especially in men.